1977
DOI: 10.1017/s0031182000062399
|View full text |Cite
|
Sign up to set email alerts
|

Patency and transmission of Filaroides hirthi infection

Abstract: Filaroides hirthi lungworm infection was diagnosed by the recovery of 1st-stage larvae from the faeces of dogs with heavy, artificially induced infections using zinc sulphate flotation. Diagnosis of low-grade natural infections was infrequently achieved. Zinc sulphate flotation was demonstrated to be about 100 times as efficient as the Baermann technique in concentrating F. hirthi larvae from dog faeces. Larvae recovered from faeces proved to be infective when fed to a pup and it was concluded that F. hirthi i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 2 publications
0
21
0
2
Order By: Relevance
“…with platinum (Agar Sputter Coater), and examined under a Zeiss DSM 926 scanning electron microscope (The Electron Microscopy Unit of the Institute of Biotechnology, University of Helsinki). Mf were extracted from the uterus of female parasites or recovered from the blood samples by using modified Knott's method (Georgi, 1985), and also studied in blood smears stained with May-Grünwald-Giemsa. For classic morphological studies, worms were fixed in 70 % ethanol, cleared in lactophenol and observed under a light microscope equipped with a drawing tube.…”
Section: Morphological Studymentioning
confidence: 99%
“…with platinum (Agar Sputter Coater), and examined under a Zeiss DSM 926 scanning electron microscope (The Electron Microscopy Unit of the Institute of Biotechnology, University of Helsinki). Mf were extracted from the uterus of female parasites or recovered from the blood samples by using modified Knott's method (Georgi, 1985), and also studied in blood smears stained with May-Grünwald-Giemsa. For classic morphological studies, worms were fixed in 70 % ethanol, cleared in lactophenol and observed under a light microscope equipped with a drawing tube.…”
Section: Morphological Studymentioning
confidence: 99%
“…When PCR was performed on the DNA extracted from the lice using established B canis species-specific 16S rDNA primers, 10 no amplicons were obtained.Even though H spiniger is classified as a chewing louse, it appears to feed more commonly on blood than on epidermal debris. 11,12 Whether the A platys DNA detected in the lice is a reflection of a recently ingested blood meal or whether the lice are in fact vectors has yet to be determined. DNA detection does not imply a transmission competence for the lice as vectors because they could have been removed from bacteraemic pups.…”
mentioning
confidence: 99%
“…We checked the literature of the 1800s and early 1900s, when the multiplicity of Tunga species was not known, to see if any early illustrations of Tunga could be referred to T. trimamillata, but all depicted T. pene trans. However, in a recent publication (Georgi & Georgi, 1991), we found photographs (Fig. 1.21 and Tables 1-6) of a gravid female classified as Tunga sp.…”
Section: Discussionmentioning
confidence: 81%